Phytotoxicity of Parthenium hysterophorus L. and Xanthium strumarium L. Extracts on Wheat Seed Germination and Cytotoxicity on Brine Shrimp Nauplii - Thapa, Chandra Bahadur; Thapa, Usha; Nepali, Baburam (Journal of Plant Resources, 2025)
Parthenium hysterophorus L. and Xanthium strumarium L. are invasive alien species found around the world. The purpose of this study is to determine the phytotoxicity of P. hysterophorus and X. stumarium leaf and root extracts on wheat seedlings and their cytotoxicity on brine shrimp [Artemia salina (Linnaeus, 1758)] nauplii. The phytotoxicity of various extracts to seedlings was evaluated using petri dishes lined with moistened filter paper, while the cytotoxicity was determined using the brine shrimp lethality assay. It was found that 85-90% of wheat seeds germinated in dichloromethane (DCM) and methanol extracts of leaf and root of P. hysterophorus and X. strumarium at lower concentrations (0.15 to 0.62 mg/mL), 50-60% at medium concentration (1.25 and 2.5 mg/mL), and 10-20% at higher concentration (5 mg/mL) after three days of incubation. Root methanol extracts were more phytotoxic to root and shoot growth in seedlings (at 0.62-5.0 mg/mL) than other P. hysterophorus root and leaf extracts. Similarly, root DCM extracts were more phytotoxic to root and shoot growth in seedlings (at 0.31-5.0 mg/mL) than other X. strumarium root and leaf extracts. Moreover, the root DCM extract was more cytotoxic (LC50: 302.93 µg/mL) to brine shrimp nauplii than the other extracts of root and leaf of P. hysterophorus. Similarly, root DCM extract was more cytotoxic (LC50: 129.16 µg/mL) to brine shrimp nauplii than the other extracts of root and leaf of X. strumarium. This study revealed that the allelochemicals/phytotoxins present in the methanol and DCM extracts of the roots and leaves of P. hysterophorus and X. strumarium were phytotoxic to wheat seeds and seedlings, as well as cytotoxic to brine shrimp nauplii. This work will help future research into the effects of allelochemicals on natural vegetation and other crop plants, as well as the carcinogenic activity of allelochemicals identified in P. hysterophorus and X. strumarium on different human cell lines.